Sub‐Inhibitory Concentrations of Florfenicol Modulate the Expression of Biofilm Formation and Antibiotic Resistance‐Associated Genes in Biofilm‐Embedded Piscirickettsia salmonis - Carla Estefanía Escalona; Natacha Santibañez; Marcos Cortés; Vicente Arriagada; Pamela Ruiz; Derie Fuentes; Alex Romero; Cristian Oliver (Journal of Fish Diseases, 2026)
Piscirickettsiosis is the most prevalent bacterial disease affecting Chilean aquaculture and responsible for the majority of mortality in salmonids. Currently, large quantities of antibiotics, predominantly florfenicol, are used in the Chilean aquaculture industry, and sub‐MIC concentrations of this antibiotic, similar to what occurs in the marine environment, have been shown to induce biofilm formation on both biotic and abiotic surfaces when sub‐MIC doses of florfenicol, raising concerns about the emergence of antibiotic‐resistant bacterial strains. Thus, the aim of this study was to evaluate whether in vitro sub‐MIC concentrations of florfenicol induce the expression of genes associated with biofilm formation and antibiotic resistance in the biofilm‐embedded P. salmonis . Interestingly, in vitro analyses showed that sub‐MIC dilutions of antibiotic significantly modulated the expression of an efflux pump acrAB and the two‐component systems cpxAR , and qseBC , as well as the antibiotic resistance‐associated genes tclor/tflor and t.flor in the biofilm‐embedded P. salmonis isolates tested. Thus, this study highlights the negative consequences of the extensive use of antibiotics in aquaculture, which can promote biofilm formation in marine bacterial pathogens, potentially facilitating the spread of resistance genes among different bacterial species in the aquatic environment and increasing the risk of reinfection within culture systems.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Effectiveness and safety of cefiderocol treatment in patients with Gram-negative bacterial infections in Spain in the early access programme: results of the PERSEUS study - Julian Torre-Cisneros; Benito Almirante; Carmen De La Fuente Martos; Pedro Rascado; Miguel Salavert Lletí; Miguel Sánchez-García; Alex Soriano; Maria Cruz Soriano-Cuesta; A. Javier Gonzalez Calvo; Andreas Karas; Jessica Sarda; Stefano Verardi; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)
Purpose We assessed the effectiveness and safety of cefiderocol in patients with Gram-negative bacterial infections, excluding Acinetobacter spp., in the early access programme (EAP) in Spain. Methods The retrospective, multicentre PERSEUS study (2018–2022) enrolled hospitalised patients with serious Gram-negative infections, except Acinetobacter spp., who received first-time cefiderocol for ≥ 72 h following requests through the EAP. Clinical cure at end of treatment, all-cause mortality at Day 28, cefiderocol use, and adverse drug reactions (ADRs) were the key outcomes. Results Overall, 261 patients were eligible for analysis. Median (interquartile range) age was 61 (49–68) years, 202 (77.4%) were male and 165 (63.2%) were in the intensive care unit. The most frequent diagnoses were respiratory tract infection (47.9%), intra-abdominal infection (14.6%), and urinary tract infection (14.6%). The median (IQR) duration of cefiderocol treatment was 10 (7–14) days. Overall, the clinical cure rate was 80.5% (210/261) and the 28-day mortality rate was 21.5% (56/261). In patients with Pseudomonas aeruginosa infection (66.7% [ n = 174], including 73 [42%] with metallo-β-lactamases), the clinical cure rate was 84.5% (147/174) and the 28-day mortality was 17.2% (30/174). Logistic regression analysis showed that prior antibiotic treatment for > 7 days (OR 0.19, 95% CI 0.05–0.56) and mechanical ventilation (OR 0.32, 95% CI 0.15–0.67) were independent negative predictive factors for clinical cure. ADRs occurred in seven patients, six events resolved, and one was fatal (toxic epidermal necrolysis). Conclusions Cefiderocol is a valuable option in the treatment of serious Gram-negative bacterial infections, particularly for those caused by P. aeruginosa . ClinicalTrials.gov NCT05789199 (Registration date: 16 February 2023).

Cefiderocol treatment for patients infected by Stenotrophomonas maltophilia, Burkholderia cepacia complex and Achromobacter spp.: subgroup analysis from the PERSEUS study - Julian Torre-Cisneros; Ricard Ferrer; Carmen De La Fuente Martos; Jessica Sarda; A. Javier Gonzalez Calvo; Stefano Verardi; Andreas Karas; Alex Soriano (European Journal of Clinical Microbiology & Infectious Diseases, 2025)
Purpose This subgroup analysis of the PERSEUS study aimed to describe the effectiveness of cefiderocol treatment in the early access programme in Spain in patients infected by Stenotrophomonas maltophilia , Burkholderia cepacia complex (Bcc) or Achromobacter species. Methods In the retrospective, observational, multicentre PERSEUS study in Spain, the effectiveness and safety of cefiderocol treatment administered for at least 72 h up to 28 days in patients infected by Gram-negative bacteria, except Acinetobacter spp., in the early access programme was investigated. Patient demographics and baseline clinical characteristics, cefiderocol use, clinical cure at end of treatment, all-cause mortality at Day 28 were the main outcomes. Results A total of 20 patients had S. maltophilia infections, and 14 patients had other rare glucose non-fermenters (Bcc 8, Achromobacter spp. 5, Ralstonia mannitolilytica 1). The median (interquartile range [IQR]) age was 60.5 (48.0–65.5) years and 49.5 (33.0–59.0) years for patients with S. maltophilia and other rare non-fermenters, respectively. The majority of patients had respiratory tract infections ( S. maltophilia 55%; other rare non-fermenters 71.4%), and median (IQR) duration of cefiderocol treatment was 10.0 (6.5–13.5) days and 8.0 (6–14) days, respectively. Clinical cure rates were 70%, 62.5% and 80.0% for patients with S. maltophilia , Bcc and Achromobacter spp., respectively. Corresponding 28-day all-cause mortality rates were 30.0%, 37.5% and 40.0%, respectively. One patient with R. mannitolilytica had clinical cure and survived to Day 28. Conclusions Cefiderocol is an important addition to the limited treatment options for patients infected by these rare glucose non-fermenting Gram-negative bacteria. Trial registration ClinicalTrials.gov: NCT05789199 (Registration date: 16 February 2023).

In vitro derived embryos produced from mares treated with intravenous clomiphene citrate - Candace C Lyman; Carlos R Pinto; Bernardo Chaves-Cordoba; Alex Wittorff; Peyton Draheim; Alejandro de la Fuente; Pouya Dini; R Jayachandra Babu; G Reed Holyoak (Journal of Equine Veterinary Science, 2023)

Influence of Harvester and Rotation of the Primary Extractor Speed in the Agroindustrial Performance of Sugarcane - Murilo Fuentes Pelloso; Bruno Fuentes Pelloso; Adriano Aparecido de Lima; Alex Henrique Tiene Ortiz (Sugar Tech, 2021)

The unfolded protein response during prostate cancer development - Alex Yick-Lun So; Erwin de la Fuente; Peter Walter; Marc Shuman; Sebastián Bernales (Cancer and Metastasis Reviews, 2009)

Vocal Repertoire of Cebus capucinus: Acoustic Structure, Context, and Usage - Julie J. Gros-Louis; Susan E. Perry; Claudia Fichtel; Eva Wikberg; Hannah Gilkenson; Susan Wofsy; Alex Fuentes (International Journal of Primatology, 2008)